Experimental investigation on the effects of different heat treatment processes on grinding machinability and surface integrity of 9Mn2V. Issue 5 (November 2015) - Dong, Dapeng; Guo, Guoqiang; Yu, Dedong; An, Qinglong; Chen, Ming
Abstract This paper investigated the grinding machinability and surface integrity of premium thread gauge material 9Mn2V in conventional surface grinding by using seeded gel (SG) abrasive (3SG80KV) under different heat treatment processes. Serious meshy segregation of carbide, excessive amounts of retained austenite, coarse and inhomogeneous distribution of material structure were significant causes of grinding burn and grinding crack. In order to improve the abrasion resistance and mechanical properties of workpiece material, cryogenic and tempering treatment was added. After adopting cryogenic and tempering treatment for two times, the disappearance of the meshy segregated carbide and network carbide was eliminated, the amount of the retained austenite content was within 4 %, and martensite became much more fine and homogeneous. The grinding experiment results indicated that workpiece material 9Mn2V could provide superior grinding integrity with the occurrence of grinding burn and grinding cracks reduced by using this process.